ELOM-080 as Add-On Treatment for Respiratory Tract Diseases – A Review of Clinical Studies Conducted in China - Fürst, Robert; Luong, Betty; Thomsen, Jörn; Wittig, Thomas (Planta Medica, 2019)
ELOM-080, also known as Myrtol, represents a distillate of a mixture of 4 rectified essential oils: eucalyptus oil, sweet orange oil, myrtle oil, and lemon oil. ELOM-080 is an approved herbal medicinal product for the secretolytic therapy and facilitation of expectoration in acute and chronic bronchitis and for the secretolytic therapy of sinusitis. Its clinical efficacy has been reported by several randomized control trials. Interestingly, in the recent past, a considerable number of clinical studies on the use of ELOM-080 as add-on treatment of different respiratory tract diseases has been conducted and published in China. As these publications were only available in Chinese, the international attention in the literature was limited. Based on the translation of these studies into English, this review aims to provide a brief overview of the studiesʼ major results, which contribute to the knowledge on the efficacy of ELOM-080 in the treatment of respiratory tract diseases: ELOM-080 was shown to be of great value as add-on treatment not only for the well-established indications bronchitis and sinusitis, but also for pharyngitis, asthma, chronic obstructive pulmonary disease, and, most importantly, otitis media. Besides this clinical evidence, this review also summarizes the great progress in deciphering the mode of action of ELOM-080 that has been made by Chinese publications.
Keywords: ELOM-080; Myrtol; phytotherapy; clinical trials; respiratory tract diseases; mode of action